Impactos Ambientales del Turismo en el Sector de Soraypampa del Distrito de Mollepata – Cusco, 2019 - 2022 - Castillo Mamani, Julio Asencio (2024)
The present work shows the social and environmental problems of Soraypampa, a sector that is the head of the Salkantay snowy basin, where hundreds of tourists arrive daily to visit the tourist attractions of the Humantay Lagoon and the Salkantay snowy four hours from Cusco. The accelerated growth of tourism demand and the lack of political strategies to deal with tourism have generated a series of social conflicts and possible environmental repercussions that were addressed in the research. In order to analyze the problems, qualitative research instruments were used, such as interviews with experts, and in this case non-probabilistic sampling was used. Former managers of the Mollepata District Tourism and Environment Area were interviewed to learn about their perceptions based on their experience in their positions. Among the main findings is that tourism in Mollepata has grown thanks to the new highway, facilitating access to the snow-capped mountain. However, challenges such as land conflicts and the lack of unity among businessmen, added to the instability of municipal policies and the lack of legal tools for environmental management, have hindered effective management of the area. It was concluded that rapid tourism development combined with insufficient governmental preparation has caused social tensions and environmental deterioration in Soraypampa because it is a vital watershed for agriculture in Mollepata and Limatambo.